Insulin Tolerance Test and Hyperinsulinemic-Euglycemic Clamp - Paschos, Georgios K. (Bio Protoc, 2013)
The two tests are used to evaluate in vivo sensitivity to insulin in mouse. The hypoerinsulinemic-euglycemic clamp provides information about the sensitivity to insulin in liver and other metabolically relevant tissues.